Canopy structural heterogeneity drives α and β species–genetic diversity correlations in a Chinese subtropical forest - Zhiliang Yao; Xia Pan; Xin Yang; Xiaona Shao; Bin Wang; Yun Deng; Zhiming Zhang; Qiaoming Li; Luxiang Lin (Plant Diversity)
Patterns and drivers of species–genetic diversity correlations (SGDCs) have been broadly examined across taxa and ecosystems and greatly deepen our understanding of how biodiversity is maintained. However, few studies have examined the role of canopy structural heterogeneity, which is a defining feature of forests, in shaping SGDCs. Here, we determine what factors contribute to α- and β-species–genetic diversity correlations (i.e., α- and β-SGDCs) in a Chinese subtropical forest. For this purpose, we used neutral molecular markers to assess genetic variation in almost all adult individuals of the dominant tree species, Lithocarpus xylocarpus, across plots in the Ailaoshan National Natural Reserve. We also quantified microhabitat variation by quantifying canopy structure heterogeneity with airborne laser scanning on 20 1-ha subtropical forest plots. We found that species α-diversity was negatively correlated with genetic α-diversity. Canopy structural heterogeneity was positively correlated with species α-diversity but negatively correlated with genetic α-diversity. These contrasting effects contributed to the formation of a negative α-SGDC. Further, we found that canopy structural heterogeneity increases species α-diversity and decreases genetic α-diversity by reducing the population size of target species. Species β-diversity, in contrast, was positively correlated with genetic β-diversity. Differences in canopy structural heterogeneity between plots had non-linear parallel effects on the two levels of β-diversity, while geographic distance had a relatively weak effect on β-SGDC. Our study indicates that canopy structural heterogeneity simultaneously affects plot-level community species diversity and population genetic diversity, and species and genetic turnover across plots, thus driving α- and β-SGDCs.